A nanogram dose of the CYP3A probe substrate midazolam to evaluate drug interactions - Halama, Birte; Hohmann, Nicolas; Burhenne, Jürgen; Weiß, Johanna; Mikus, Gerd; Haefeli, Walter E. (Clinical pharmacology & therapeutics, 2013)
The objective of the study was to establish an in vivo method for assessing cytochrome P450 3A (CYP3A) activity using therapeutically inert nanogram doses of midazolam. We administered four escalating single doses of oral midazolam (0.0001-3 mg) to 12 healthy participants, stratified according to CYP3A5 carrier status, to assess pharmacokinetics linearity. We then evaluated the interactions with the CYP3A inhibitor ketoconazole (400 mg q.d.) after nanogram and regular doses of midazolam. Area under the plasma concentration-time curve (AUC) and peak plasma concentration (Cmax) were linear over the entire range of doses. Ketoconazole reduced midazolam oral clearance by 92.8%. AUC and Cmax increased by 1,540 and 363%, respectively. CYP3A5 carrier status had no influence on midazolam oral clearance or its inhibition by ketoconazole. This is the first study showing that midazolam pharmacokinetics is linear in a 30,000-fold concentration range, and therefore that nano- and microgram doses of midazolam can reliably predict the pharmacokinetics of midazolam in therapeutic doses and can be used to assess CYP3A activity even in the presence of strong CYP3A inhibitors. Clinical Pharmacology & Therapeutics (2013); 93 6, 564-571. doi:10.1038/clpt.2013.27